Restoration of Videos Degraded by Local Isoplanatism Effects in the Near-Infrared Domain - Lemaitre, Magali; Laligant, Olivier; Blanc-Talon, Jacques; Mériaudeau, Fabrice (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2009)
When observing a scene horizontally at a long distance in the near-infrared domain, degradations due to atmospheric turbulence often occur. In our previous work, we presented two hybrid methods to restore videos degraded by such local perturbations. These restoration algorithms take advantages of a space-time Wiener filter and a space-time regularization by the Laplacian operator. Wiener and Laplacian regularization results are mixed differently depending on the distance between the current pixel and the nearest edge point. It was shown that a gradation betweenWiener and Laplacian areas improves results quality, so that only the algorithm using a gradation will be used in this article. In spite of a significant improvement in the obtained images quality, our restoration results greatly depend on the segmentation image used in the video processing. We then propose a method to select automatically the best segmentation image.